2015
DOI: 10.1080/21645698.2015.1026524
|View full text |Cite
|
Sign up to set email alerts
|

Expression of synthetic human tropoelastin (hTE) protein inNicotiana tabacum

Abstract: ABSTRACT. Plant molecular farming (PMF) is an important growing prospective approach in plant biotechnology; it includes production of recombinant pharmaceutical and industrial proteins in large quantities from engineered plants. Elastin is a major protein component of tissues that require elasticity, it helps keep skin smooth as it stretches to allow normal. Elastin is used as a raw material for the cosmetic industry. In this work, we aimed to use plant as a bioreactor for the expression and production of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…In addition, transient expression is genome integration-independent strategy, which will not be affected by position effects existing in stable transformation, once that the expression vector remains an episomal DNA molecule [22]. Our result is in accordance with previous works, which indicated that agroinfiltration could efficiently resulted in transferring of Agrobacterium into the plant leaves and robust expression of recombinant proteins [24,[52][53][54]. In our study, the infiltration of agrobacterium into the intercellular space of the leaf was performed with syringe method (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, transient expression is genome integration-independent strategy, which will not be affected by position effects existing in stable transformation, once that the expression vector remains an episomal DNA molecule [22]. Our result is in accordance with previous works, which indicated that agroinfiltration could efficiently resulted in transferring of Agrobacterium into the plant leaves and robust expression of recombinant proteins [24,[52][53][54]. In our study, the infiltration of agrobacterium into the intercellular space of the leaf was performed with syringe method (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Process Biochemistry 70 (2018) [45][46][47][48][49][50][51][52][53][54] conditions consisting of 25°C/16-h light and 20°C/8-h dark and 40-65% relative humidity for four to six weeks. At this stage, the plant has at least six fully developed true leaves and no visible flower buds.…”
Section: Plant Materials and Agroinfiltrationmentioning
confidence: 99%
“…Unlike other proteins, a single gene known as ELN, which is localized on chromosome 7 and expressed by different cell types throughout development, codes for elastin in humans [38,59,60]. As a result of alternative splicing, different isoforms of the soluble tropoelastin protein have previously been identified, suggesting a potential regulatory mechanism in the expression of this gene.…”
Section: Elastin and Alternative Splicingmentioning
confidence: 99%
“…A band corresponding to~70 kDa was detected during electrophoresis of fresh leaf extracts using an antibody against tropoelastin. However, recombinant tropoelastin degraded into two smaller molecular weight peptides when leaf extracts were frozen (Abdelghani et al, 2015). As the instability of protein going through freeze thaw of the leaf tissues will create a problem for potential harvesting and storage, recombinant tropoelastin directed to seeds may be more suitable, since recombinant protein can be stably stored in the seeds (Weichert et al, 2016).…”
Section: Elastin-based Scaffold Protein Produced From Plantsmentioning
confidence: 99%